Peran Akuntansi Dalam Mewujudkan Good Governance (Studi Kasus Pada Desa Sukowiryo Kabupaten Bondowoso) - Niken Wahyu Cahya Christianti; Yulinartati; Astrid Maharani (LPPM POLITEKNIK LP3I BANDUNG, 2022)
This study aims to determine the role of accounting in realizing Good Governance. The principles of Good Governance used in this research are accountability, transparency, responsibility, strategic vision, efficiency and effectiveness. The type of research used is qualitative research. Data collection techniques using interview techniques, observation, literature study, documentation techniques, internet searching. The results show that accounting has a very important role in realizing good governance. The role of accounting in realizing accountability is a benchmark for assessing the performance of Sukowiryo Village, Bondowoso Regency, and can also support public sector organizations to account for all tasks and authorities carried out in accordance with the goals that have been set. In realizing transparency, accounting can guarantee the accuracy and truth of the information disseminated in the village. Meanwhile, in realizing responsibility, accounting can help accountability for the use of APBDes and RKP-Village funds in Sukowiryo Village, Bondowoso Regency. The role of accounting in realizing the strategic vision is to assist in the preparation of the RKP-Village which can be used to consider costs with the aim of achieving the targets to be set. The role of accounting in realizing efficiency and effectiveness is to be able to assist the process of budgeting funds so that they can be carried out optimally. Barriers to the role of accounting in realizing good governance are not too serious for the sustainability of the program of activities carried out, namely human resources who do not understand accounting, but it is not a big problem to realize good governance in society. everything can be handled properly by conducting socialization and accounting training.